The Use of Video as an Audio-Visual Material in Foreign Language Teaching Classroom - Nehru P. Pongsapan (Jurnal Keguruan dan Ilmu Pendidikan, 2017)
In recent years, a great tendency towards the use of technology and its integration into the curriculum has gained a great importance. Particularly, the use of video as an audio-visual material in foreign language teaching classrooms has grown rapidly because of the increasing emphasis on communicative techniques, and it is obvious that the use of video is a great help for foreign language teachers in stimulating and facilitating the target language. Keeping all this in mind, the purpose of this article was to provide the required information for foreign language teachers (FLT) so that they can make use of video efficiently in the classroom. Reasons for video implication in FLT classroom and teacher’s role in this process have been revealed along with some practical techniques for video implication.